OPTIMATION OF FENTON CATALYST FROM GRINDING SPARK OF CARBON STEEL FOR DEGRADING METHYLENE BLUE AS POLLUTANT MODEL OF SYNTHETIC COLOR SUBSTANCE - Aditya Sanjaya, Fathan
The Citarum River plays an important role for the people of West Java and Jakarta as a source of clean water, irrigation for agriculture and hydroelectric power. However, the Citarum river is classified as one of the most polluted rivers in the world because of its very high level of pollution, especially in the textile industry centers. This is because the textile industry uses synthetic dyes such as dyes azo classified as Persistent Organic Pollutants (POPs) because they cannot be degraded by conventional waste treatment methods. Therefore, an alternative method is needed that can remove azo dyes from textile industry wastewater. One technology that can be a solution is Advanced Oxidation Processes (AOPs) technology based on the Fenton reaction because it is able to degrade all organic pollutants into H2O and CO2. In this study, grinding powder which is a waste from the carbon steel used as a Fenton heterogeneous catalyst to degrade methylene blue (MB) as a model for synthetic dyes. The type of carbon steel used (St37 and K100) and the amount of catalyst was varied to obtain the best conditions for degrading synthetic dyes. In addition, isopropanol was used in this study to determine the type of radicals that play a role in the MB degradation process, because isopropanol can function as a scavenger for the formation of hydroxyl radicals. Based on the estimation of spark using the colour-ratio pyrometry and digital imaging temperature spark produced from the grinding process St37 (1434 ± 20,1°C) can reach the melting temperature of St37 (1420 - 1460°C), thus encouraging rapid solidification. Meanwhile spark produced from the K100 grinding process (1418 ± 51,61°C) can reach the melting temperature of K100 (1450 - 1510°C). This shows that the average K100 has not yet reached the melting point to achieve rapid solidification. The difference between St37 and K100 in temperature prediction will determine whether the powder will be spherical or not as a result of rapid solidification. Based on testing with UV-Vis spectroscopy, it is known that the grinding powder of St37 has a better catalytic activity than K100 because the grinding powder of St37 has a structure of Fe/Fe2O3 core-shell which can activate hydrogen peroxide to produce more hydroxyl radicals thereby speeding up the reaction and has a spherical so it has a higher surface area to activate hydrogen peroxide to produce hydroxyl radicals. Based on the parameters of changes in the mass variation of the catalyst, the catalyst with a mass of 0.8 g was able to provide overall better degradation performance compared to the other variations, namely 1.2 g and 0.4 g. The catalyst with a mass of 0.8 g was able to degrade up to ± 22% in 120 minutes and the lowest performance was owned by the 0.4 g catalyst which was only able to degrade up to ± 15% in 120 minutes. Based on testing with isopropanol, it is known that the degradation ability of grinding powder decreases with increasing isopropanol concentration. This shows that hydroxyl radicals are radicals that play a role in the MB degradation process because isopropanol is scavenger that specifically inhibits the formation of hydroxyl radicals in solution. .